Time-dependent behaviour of composite beams with blind bolts under sustained loads. (September 2015) - Ban, Huiyong; Uy, Brian; Pathirana, Sameera Wijesiri; Henderson, Ian; Mirza, Olivia; Zhu, Xinqun
Abstract: The use of blind bolts in steel–concrete composite beams is beneficial for promoting sustainable design and for retrofitting existing steel structures. This paper presents an experimental study as well as finite element (FE) modelling analyses for the time-dependent behaviour of composite beams with blind bolts subjected to sustained loads. Four full-scale simply supported beams utilising different types of bolts and studs were tested under long-term static loads. The mid-span deflections were monitored for a period of over 260 days. Short-term push-out tests were also carried out on the connectors used in the composite beams, and their slip deformation was recorded for determining the initial stiffness. The experimental results were modelled by using a three-dimensional FE model, in which the creep of the concrete was simulated through defining a viscoelastic response and the shrinkage of concrete was incorporated by means of notional thermal expansion. The FE model was validated against the experimental results reported herein and other independent results of composite beams using conventional welded studs reported elsewhere, and it was subsequently applied to carry out parametric studies. An extensive body of parameters was considered to clarify their effects on the time-dependent behaviour of composite beams with blind bolts, including the mechanical properties and configuration details of shear connectors, the concrete strength, the loading conditions, the span-to-depth ratio and the reinforcement ratio. It was demonstrated that the time-dependent behaviour was sensitive to the stiffness and the bolt-to-hole clearance of connectors, and some other parameters also possessed effects with different degrees. The research findings implied that using blind bolts in composite beams was beneficial to the time-dependent response due to their relatively lower deflections resulting from the creep and shrinkage of the concrete over time. The outcome may provide an important basis and guidance for designing such composite beams when considering their long-term response with time effects. Highlights: Long-term tests on composite beams with blind bolts are carried out. Push-out tests on two types of bolted shear connections are undertaken. A FE model is valid and utilised to undertake numerous parametric analyses. The time-dependent behaviour is sensitive to connectors' stiffness and bolt-to-hole clearance. Using blind bolts in composite beams is beneficial to the time-dependent response.